STORYTELLING BERBANTUAN MEDIA GAMBAR PADA PEMBELAJARAN BERCERITA SISWA SEKOLAH DASAR KOTA CIREBON - Mega Mugi Rahayu, - (2020)
From the limitation of the data, the researcher e amined the storytelling method by using the image as the media in the learning of storytelling in Grade 1 students of SD Negeri Kanggraksan. The purpose of this research is to know the overview of the process and the ability of the students in speaking especially in storytelling with the media image-assisted storytelling method. The research method used in this study is research on Quasi e periments. The subject of this study is class I which amounted to 20 students and the observer partner is the teacher in the class. The results of the study showed that there is a significant increase in the learning outcomes and in the students' storytelling skills. The image media that has been used with the acquisition of the value of their practice results in a storytelling previously was only 5.35 (the optimal value e pected), and then increased to be 16.05 (the optimal value) after following the method of storytelling learning by using the image media. Judging by the increasing storytelling skills of SD Negeri Kanggraksan Kota Cirebon students, it can be concluded that the image media-assisted storytelling method can improve students' speaking skills especially in storytelling skills.